PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA ORGANISASI - Eko Boedhi Santoso; Nilawati Fiernaningsih; Rizky Kurniawan Murtiyanto (Adbis: Jurnal Administrasi dan Bisnis, 2018)
Organizational culture is a habit, norms, rules that are understood and agreed upon by all members of the organization. Organizational culture is more to the right thing that must be obeyed and implemented and bad things are prohibited and will be sanctioned if there is a violation. Organizational culture is very embedded in the organization, both in carrying out work, communicating with fellow members and other habits that are hereditary. Based on this, the organizational culture is important or has an important role in the overall activities of the organization. In this study, the hypothesis raised was the alleged influence of organizational culture on organizational performance. So, to prove the hypothesis, an analytical tool is developed that can measure and know. Information is obtained by questionnaire method distributed to respondents. Hopefully, the results of this study contribute to the company as the object of research, the wider community, and further research on similar topics. This research is also expected to provide support forthe theory of Human Resource Management